Evaluasi Pengakuan Pendapatan Jasa Kontrak Konstruksi Menurut PSAK No. 34 pada PT. Nastek Mustika Abadi - Dewi Agustya Ningrum; Nora Vista Arafah; Darno Darno; Wulan Purnamasari (Jurnal Pajak Vokasi (JUPASI), 2021)
PT Nastek Mustika Abadi is a company that provides construction services in the field of services such as manufacturing iron machines or factory machinery, making electrical installations and building assets such as buildings, tunnels and roads, Based on its characteristics this business is a long-term business, due to contract activities that generally occur completed in different accounting periods as part of the Company's Financial Report. The methods and data analysis techniques made in this study, namely descriptive analysis, are studies that only collect, compile, clarify and interpret data so that they get a clear picture of the problem being studied. The type of data used in the observation is in the form of quantitative data, namely data in the form of numbers or nominal that are in the financial statements of a service company in the city of Surabaya.Service income that has been made an invoice is recognized to be the gross bill of the employer, in recording the company's activities that are not quite in sync with PSAK No. 34 and using the percentage completion method so that capital turnover is faster than using the completed contract method. Construction cooperation agreement with the client, based on the agreed work contract. In measuring the value of income in companies, it has been synchronized by PSAK, which is measured at fair value. This value will be presented in the company's financial statements. The accounting treatment for construction contracts at PT Nastek Mustika Abadi, uses PSAK No. 34 as the basis. The accounting treatment of construction contracts at PT Nastek Mustika Abadi is quite appropriate but the journal made by the company is not appropriate with PSAK No. 34 at PT Nastek Mustika Abadi, revenue from sales is recognized when providing goods and services to customers. The company uses the percentage settlement method to recognize revenue from contractor services. So it can be concluded that the recording of the right journal in accordance with PSAK No. 34.